Kajian Pengaruh Ketebalan Lapisan P3HT Pada Sel Surya Organik Berbasis Bahan Organik Dan Polimer - Fahru Nur Rosyid, Fredicha Arya N., Agus Supriyanto (Jurnal Teori dan Aplikasi Fisika, 2013)
Organic solar cells with structure of FTO / PEDOT: PSS/P3HT/Klorofil/Al has been made. Fabrication of the active layer organic solar cells using spin coating method, while the counter electrode fabricated using evaporator method. Variations performed on P3HT layer with thickness variation is 1 layer, 3 layers, 5 layers and 7 layers. Characterization of optical properties in the visible conducted using UV-VIS spectrometer, while the electrical properties characterictics using the IV Meter El Kahfi in the dark and under irradiation. Characterization of organic solar cells was measured by using a Keithley 2602. Organic solar cell I-V characteristics measured tested under illumination with an intensity of 1000 Watt/m using xenon light in the area of 10 mm. Based on the results obtained organic solar cells with 7 layers of P3HT shows the I-V characteristics of the best results compared to other P3HT layer thickness. Keywords: organic solar cell, P3HT, klorofil, spin coating